THE EFFECTS OF DIFFERENT SMOKING TEMPERATURE AND TIME ON THE CONTENT OF WATER, FAT AND SALT OF SMOKE TILAPIA (Oreochromis niloticus) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Smoking fish is a method of processing to extend the shelf life of the product. To overcome the decline in the quality of tilapia is through a cold smoking process. Cold smoking has a longer shelf life than fish smoked with hot smoking. This study aims to determine the effect of temperature and smoking time on the quality of smoked tilapia using the cold smoking method. The interaction of temperature treatment and smoking time in the smoking process affects the characteristics of the water, fat, and salt content of smoked tilapia. Smoked tilapia produced by a combination of temperature treatment and smoking time has a moisture content of 12.73-20.46%; fat with an average of 16.48-27.17%; and salt by 3.30-4.68%. Temperature treatment of 50-55oC for 48 hours gave a lower moisture content value of 12.73%. The results of this study indicate that differences in temperature and smoking duration affect the moisture, fat, and salt content of smoked tilapia.